Solve for p 6p+2=9p-1

Math
6p+2=9p-1
Move all terms containing p to the left side of the equation.
Tap for more steps…
Subtract 9p from both sides of the equation.
6p+2-9p=-1
Subtract 9p from 6p.
-3p+2=-1
-3p+2=-1
Move all terms not containing p to the right side of the equation.
Tap for more steps…
Subtract 2 from both sides of the equation.
-3p=-1-2
Subtract 2 from -1.
-3p=-3
-3p=-3
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3p=-3 by -3.
-3p-3=-3-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3p-3=-3-3
Divide p by 1.
p=-3-3
p=-3-3
Divide -3 by -3.
p=1
p=1
Solve for p 6p+2=9p-1

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top